A cross-generational comparison of smartphone addiction among Gen X and Gen Y smartphone users in Malaysia - Mohd Kamal Othman; Mohd Yasin Mohd Amin (Intelektual Pustaka Media Utama, 2022)
This study reported the prevalence of smartphone addiction among Gen X and Gen Y in Sarawak, Malaysia. This study compared the two generations, X and Y, on smartphone addictive behaviour. It is important to understand their addiction to smartphones. Two hundred thirty-six participants were recruited using a Facebook advertisement, consisting of 122 males and 114 females aged 16 to 55. The smartphone addiction scale-malay (SAS-M) was used to assess smartphone addiction. The data was analysed using IBM SPSS. The result shows that Gen Y is more addicted to a smartphone than Gen X for all components of SAS-M, but there is no significant difference between female and male users for both generations in smartphone usage. In addition, there is a significant difference in the cyberspace-oriented relationship between Gen X and Gen Y. Furthermore, Gen Y had lost control of the use of smartphones compared to Gen X, which reflects the overuse and primacy components that lead to daily life disturbances. Positive anticipation and withdrawal were also observed between the two generations. In conclusion, there is a significant difference between Gen X and Gen Y in smartphone addictive behaviour, implying that Gen Y is a more compulsive user than Gen X. It is important to understand this addictive behaviour and provide an intervention measure to ensure that this will not become a psychological issue. The intervention measure is important to improve mental health and psychological wellbeing.